Preclinical Testing of Drug-Induced Proarrhythmia: Value of Transgenic Models - Fabritz, L.; Breithardt, G.; Kirchhof, P. (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2007)
Drug-induced proarrhythmia is a serious medical problem that causes relevant morbidity and mortality. It is also a relevant problem for the development of novel pharmacological compounds. Therefore, there is a need for sensitive, specific and high-throughput preclinical tests to detect a risk for drug-induced proarrhythmia early in the development of new drugs. The review focuses on the potential role of transgenic models with altered repolarisation but without overt structural heart disease for drug-induced proarrhythmia screening. Today, selected murine models with alterations in K+, Na+ channels and ankyrin are available. In the future, transgenic rabbit and Zebra fish models may also be used.
Keywords: action potential prolongation